Distal snuffbox versus conventional radial artery access: An updated systematic review and meta-analysis. Issue 4 (July 2022) - Rigatelli, Gianluca; Zuin, Marco; Daggubati, Ramesh; Vassilev, Dobrin; Zuliani, Giovanni; Nguyen, Thach; Roncon, Loris
Background: A comprehensive comparison of available data in terms of vascular complications between distal and conventional transradial access is still partial and a net benefit of such approach has not yet been clearly demonstrated. Objective: To provide an updated comparison of complications between distal and conventional transradial access used to perform coronary angiography and/or percutaneous coronary intervention performing a systematic review and meta-analysis. Data sources: Data were obtained searching MEDLINE, Scopus, and Web of Science for all investigations published any time to December 22, 2020 reporting a comparison between distal and conventional transradial access. The occurrence of radial artery occlusion was chosen as the primary outcome while the hematoma at access site and spasm as secondary and tertiary outcome, respectively. Study eligibility criteria: Case-control studies comparing distal and conventional transradial access for coronary angiography and/or percutaneous coronary intervention. All studies included adult patients aged at least 18 years. Study appraisal and synthesis methods: Overall, 7073 patients (mean age 57.9 and 58.4 years for distal and conventional transradial access, respectively), were analyzed. The rate of radial artery occlusion was significantly lower in the distal compared with the conventional group (2.1% vs 4.6%, p  < 0.001). The pooled analysis, based on a fixed effect model confirmed a lower relative risk of occlusion when distal access is used (RR: 0.46, 95% CI: 0.31–069, p  = 0.002, I 2  = 0%). Conversely, no differences in the risk of developing a hematoma at the access site or in the occurrence of a radial artery spasms were observed comparing the two groups (RR: 0.65, 95% CI: 0.37–1.13, p  = 0.12, I 2  = 0% and RR: 0.88, 95% CI: 0.48–1.63, p  = 0.001, I 2  = 0%, respectively). Limitations: Only eight case-control studies met inclusion criteria Conclusion: This metanalysis confirmed a lower risk of radial artery occlusion using distal access and comparable performance in terms of hematoma, and radial artery spam risk.